The expansion of Multilateral Development Banks: a game approach - Pereira, Rafael Antonio Anicio (2021)
What are the determinants of cooperation between countries regarding development finance? This dissertation deals with this broad question by looking at the evolution of Multilateral Development Banks (MDBs) over the last decades. Created through the association of national states to provide funds for development projects and programs, MDBs are based on a general financial model that has attracted almost all countries over the years and still keeps its significance. While scholarship has progressed considerably to explain the functioning and the evolution of a great diversity of MDBs, it still presents theoretical and scope-related limitations. Authors working within the existing perspectives found in the literature tend to emphasize only a part of the variables that influence MDBs to the detriment of others, which does not allow us to satisfactorily answer an important question: what are the factors causing these institutions to grow, and why can they sometimes stagnate? The goal of this dissertation is to contribute to the literature by developing a new analytical framework, inspired by game theory, that enables us to approach MDBs without relying on restrictive assumptions, and thereby provide a comprehensive explanation for their expansion. Based on this analytical framework, I test the hypothesis that MDB expansion depends on the combination of strategies of two groups of MDBs members and their mutual dependence in two different games. I analyze data regarding three important institutions through periods that involve practically all their trajectories. Generally, the results are in accord with what is expected for coordination and imposition games.